Social Media and Social Networking Applications for Knowledge Sharing among Academics in Nigeria - Gamji, Musa Bara U. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The usage of social media and social networking applications to communicate or share ideas among people is one of the trending areas in communication and new media research. This research sought to investigate the usage of Social Media and Social Networking applications as knowledge sharing technologies among lecturers, or with students. The study used convenient sample method to select respondents through a multi-stage sampling procedure to gather data from 1047 respondents across 13 academic faculties at Ahmadu Bello University (ABU) in Zaria, Nigeria, who responded to a survey questionnaire instrument. SPSS and NVivo data analysis programs were used for the analysis of both qualitative and quantitative data. Crosssectional design within the action research framework was conducted using mixedmethod; with structured questionnaires and in-depth interviews. Diffusion of innovation, unified theory of acceptance and use of technology theories formed the conceptual framework of the study. Key Findings reveal that, the greatest challenges faced by Nigerian academics in using social media and social networking applications include low interconnectivity and insufficient electricity supply. In addition, the academic staff of the Ahmadu Bello University Zaria were influenced to use the Social Media and Social Networking applications by the technological factor followed by the individual factor, and that there is no significant relationship between the participants' gender and the use of the technologies. The COVID 19 pandemic period according to the findings has increased the use of the social media and social Networking applications among the academics of Ahmadu Bello university Zaria. Three out of the four hypothesis were supported by the qualitative data of the findings while hypothesis 1 (H1) stands unsupported.

ÖZ: İnsanlar arasında iletişim kurmak veya fikir paylaşmak için sosyal medya ve sosyal ağ uygulamalarının kullanımı, iletişim ve yeni medya araştırmalarında yaygın çalışma alanlarından biri haline gelmiştir. Bu nedenle, bu araştırma, sosyal medya ve sosyal ağ uygulamalarının öğretim elemanlarının kendi meslektaşları ve öğrencileri arasında hangi oranda ve nasıl kullanıldığını araştırmayı amaçlamıştır. Çalışmanın evreni, çok aşamalı bir örnekleme prosedürü ile belirlenmiştir. Nijerya, ABU Zaria Üniversitesi’ndeki 13 fakültede anketi cevaplayan 1047 kişinin verileri temel alınmıştır. Nitel ve nicel verilerin analizi için SPSS ve NVivo programları kullanılmıştır. Çalışmada, anket ve derinlemesine görüşmelerle toplanan verilere dayanan karşılaştırmalı karma bir araştırma yöntemi izlenmiştir. Bu tezde argümanlar, Yeniliklerin Yayılması ve Teknoloji Kabul ve Bütünleşik Davranış Kuramları etrafında gelişmiştir. Analizler, veri enflasyonu, zayıf internet bağlantısı ve elektrik kesintilerinin akademisyenlerin sosyal medya ve sosyal ağ uygulamalarını kullanırken karşılaştıkları en büyük engeller olduğunu ortaya çıkarmıştır. Ayrıca bu akademisyenlerin bilgi paylaşım uygulamalarını kullanmalarında teknolojik faktörün yanı sıra bireysel faktörlerin de engeller arasında olduğu ama cinsiyet ile teknoloji kullanımı arasında anlamlı bir ilişki olmadığı da tespit edilmiştir. COVID 19 pandemi sürecinin bu uygulamaların akademisyenler arasında kullanımını olumlu yönde etkilediği de gözlemlenmiştir.
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2021. Supervisor: Assoc. Prof. Dr. Nurten Kara.
Keywords: Communication and Media Studies Department; Social networks--Social Media--Communication; Social Media; Social Networking Applications; Knowledge Sharing; Academics